THE INFLUENCE OF IMPORT TARIFF TOWARDS INDONESIAN BALANCE OF TRADE AND NATIONAL INCOME - Malik, Nazaruddin (Journal of Innovation in Business and Economics, 2011)
This study tries to explain the influence of import tariff to Indonesian balance of trade and national income. The analysis was made by applying a dynamic linier model. The result showed that the imposing of import tariff has a positive and significant influence to the raising of balance of trade surplus in a long term. The import tariff on commodity of agriculture and manufacture have also positive influence to the growth on balance of trade, however the sector that give a significant value is agriculture sector. The surplus growth on balance of trade gives positive and significant influence to the national economic growth.